(untitled) - I Gede Made Artha Dharmakarja (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study aims to determine college student perceptions of government debt based on their knowledge and expectations. During the political campaign in Indonesia in 2019, the pros and cons of government debt policy became a debate. Students use their knowledge and expectations sourced from political speeches and news to conduct a protest. This research uses purposive sampling and the questionnaire is used as a method of collecting data, and then analyzed using logistic regression. The total sample was 228 college students. The result shows that knowledge and expectations have a positive effect on the perception of government debt, both simultaneously and partially. The biggest knowledge factor shows that government debt information is actually mostly obtained from non-government sources. While expectations show concern over the increasing government debt. The biggest perception is that debt reduces government credibility.